Cultural Capital Apparatus: Relasi Kuasa Bisnis dan Media dalam Globalisasi - Muzayin Nazaruddin (Jurnal Komunikasi, 2006)
In front of global capitalism, the state is no longer be a main power. The sources and power relations upon the society are getting more complicated. But, one thing we have to say directly, power transition from state to business power which is run by multinational corporations is now happening. This transition brings neoliberalism ideology as the only one epistemology that reducts human as homo economicus. In this historical context, mass media and entertainment industries become a part of business power along with their orientation to accumulate the capital. Media and entertainment industries become one of capital apparatuses, cultural capital apparatus to be exact. This thesis can be proved by a main-general phenomenon: media industries are becoming more and more concentrated, and the dominant players are the huge global media conglomerates, This media conglomeration become a clarifier for the interest's bias of the stakeholders in media reporting, media content uniformity, decline of the journalistic's quality, media information commercialization, and orientation to the entertainment programs. Media content uniformity barely campaign banalitation of thought, hedonism, consumerism and commercialization in almost all parts of life. All of them is in the line with the neoliberal ideology that being carried by the media itself.